Central foundation of the right against self-incrimination - Heloisa Rodrigues Lino de Carvalho (Revista Brasileira de Direito Processual Penal, 2018)
Non-self-incrimination, immanent especially in Constitutional Criminal Procedural Law, is an individual and fundamental human right. Its observance is mandatory in criminal prosecution, provided for in important international human rights documents, as well as in most of the democratic Constitutions. Employing a scientific methodology by means of bibliographical research and theoretical deductive method, the objective is to analyze its central foundation, to be able to outline its scope more accurately. The main driver for its existence is human dignity, whose most solid aspect is a person’s mental and moral integrity. This is violated when the individual faces possible unpleasant disjunctives, marked by the possibility of giving rise to negative consequences. The person ends up either opting to remain silent or testify and, in this case, they may self-incriminate (admitting imputation, whether true or not) or by lie. This transgresses human nature, since we have difficulty admitting our own faults and bearing with the consequences thereof. The prohibition of compelling the accused to issue a statement and attributing any negative consequences to their silence is an undeniable consequence of that right. However, its applicability in different concrete cases incites many controversies. The outline of its real foundation aims at contributing with subsidies for coherent solutions.